Legalitas Penerbitan Akta Kelahiran Anak Yang Dilahirkan Dari Perkawinan Yang Tidak Dicatatkan - Fitri, Ervina; Hufron (CV. Era Digital Nusantara, 2023)
This study aims to analyze the legality of issuing birth certificates for children born out of unregistered marriages, this study uses normative juridical research methods, and uses literature that is relevant to the study of making child birth certificates for unregistered marriages. The main legal basis comes from statutory regulations, and the secondary legal basis is in the form of literature, documents, opinions of legal experts. This is also related to the legality of issuing birth certificates for children born from unregistered marriages. The results of this study are related to the making of birth certificates for children born out of marriage which are not recorded through a Statement of Absolute Responsibility (SPTJM) which refers to Permendagri No. 9 of 2016. Birth certificates for children born without marriage registration that are not listed on the Family Card are only recorded as children of a mother. Through this research, it is hoped that it can provide a better understanding of the legality of issuing birth certificates for children resulting from marriages that are not legally registered. The results of this research can make an important contribution to the development of more inclusive legal policies and better protection of children's rights.